2011
DOI: 10.1016/j.bbrc.2011.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum is a main localization site of mTORC2

Abstract: The Akt kinase is a critical effector in growth factor signaling. Activation of Akt driven by the growth factor dependent PI3K (phosphatidylinositol-3-OH kinase) is coupled to the plasma membrane translocation and phosphorylation of Akt on two sites by PDK1 (phosphoinositide-dependent protein kinase-1) on Thr-308 and by mTORC2 (mammalian Target Of Rapamycin Complex 2) on Ser-473. In our study we examined the sub-cellular localization of mTORC2 and identified that this kinase complex predominantly resides on en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 27 publications
6
67
2
2
Order By: Relevance
“…It has been recently reported that a proper protein folding is critical in the assembly of mTORC2 and that a single amino acid substitution on rictor has precluded the assembly of mTORC2 (23). Because the endoplasmic reticulum has been identified as the main localization site of mTORC2 (27), this phosphorylation-dependent degradation pathway might be linked to proper protein folding monitoring by endoplasmic reticulum quality control that tags mTORC2 containing the non-phosphorylated form of SIN1 for disintegration and lysosomal degradation. A disintegration step in this process is supported by the observation that the abundance of SIN1 and rictor but not of mTOR and mLST8 is highly sensitive to phosphorylation of SIN1 on Ser-260.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that a proper protein folding is critical in the assembly of mTORC2 and that a single amino acid substitution on rictor has precluded the assembly of mTORC2 (23). Because the endoplasmic reticulum has been identified as the main localization site of mTORC2 (27), this phosphorylation-dependent degradation pathway might be linked to proper protein folding monitoring by endoplasmic reticulum quality control that tags mTORC2 containing the non-phosphorylated form of SIN1 for disintegration and lysosomal degradation. A disintegration step in this process is supported by the observation that the abundance of SIN1 and rictor but not of mTOR and mLST8 is highly sensitive to phosphorylation of SIN1 on Ser-260.…”
Section: Discussionmentioning
confidence: 99%
“…A role of the endoplasmic reticulum in regulation of mTORC2 is becoming more evident. A recent study has indicated the predominant localization of mTORC2 in the endoplasmic reticulum (28). Importantly, the functional regulation and association of mTORC2 with ribosomes have been reported (29,30).…”
mentioning
confidence: 99%
“…Moreover, the signaling from growth factor does not change the ER localization of mTORC2 as well as its translocation to the plasma membrane. Besides it was suggested that the mTORC2-dependent phosphorylation of Akt on S473 occurs on the surface of ER [37]. These observations raise many interesting questions regarding the regulation of TORC2 and its ribosomal interactions, but it also indicates that additional levels of interplay between TORC2 and TORC1 may exist, as both complexes are linked to the process of ribosome biogenesis.…”
Section: Signaling Up and Downstream Of Mtorc2mentioning
confidence: 99%
“…Thus, upon nutrients and energy availability mTORC1 is recruited to lysosomes where it could be fully activated [36] and where it functions to suppress autophagy. Unlike mTORC1, mTORC2 according to the most recent data localizes predominantly in ER compartment where it could directly associate with ribosomes [37,38]. Additionally, some data evidence that mTOR may actually be a cytoplasmic-nuclear shuttling protein.…”
Section: The Tor Complexes Mtorc1 and Mtorc2mentioning
confidence: 99%